A computer-assisted robotic platform for vascular procedures exploiting 3D US-based tracking. Issue 1 (1st January 2016) - Mura, Marco; Parrini, Simone; Ciuti, Gastone; Ferrari, Vincenzo; Freschi, Cinzia; Ferrari, Mauro; Dario, Paolo; Menciassi, Arianna
Abstract: Background: Cardiovascular diseases are the first cause of death globally: an estimated 17.5 million people died in 2012. By combining the benefits of magnetic navigation and ultrasound (US) imaging, the authors proposed a robotic platform (i.e. the MicroVAST platform) for intravascular medical procedures. Methods: A 3D imaging US-based tracking algorithm is implemented for the navigation of a magnetic-dragged soft-tethered device. Tests were performed to evaluate the algorithm in terms of tracking error and precision of locomotion. Results: The 3D imaging US-based algorithm tracked the endovascular device with an error of 6.4 ± 2.8 pixels and a mean displacement between the endovascular device and the preoperative path of 13.6 ± 4.5 mm (computational time of 12.2 ± 1.5 ms and 30.7 ± 6.1 matched features). Conclusions: The MicroVAST platform includes innovative solutions for navigation allowing for an assisted magnetic locomotion of medical devices in the cardiovascular district by combining a 3D imaging US-based tracking algorithm with pre-operative data.